STRATEGI READING ALOUD DALAM MENUMBUHKAN MINAT MEMBACA SISWA DI KELAS IV SDN PANCORAN 07 PAGI - Annasyah Kamila; Rudi Ritonga (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2022)
This research discussed of the strategy reading aloud for caused to emerge student interest in reading at the fourth grade of SDN Pancoran 07 Pagi. Because reading is one of the language skills that needed in daily life. Especially in education. This research aimed to describe the factors that influence the reading interest of fourth grade students at SDN Pancoran 07 Pagi and to explain the implementation of strategy reading aloud that have been carried out by the teacher for developing theirs reading interest. The method that been used in this research is qualitative with descriptive approach which means the researcher describes the results of the research that has been carried out in a narrative and costumized based on the conditions that already found out during the study. The results obtained through interview, questionnaires, and documentation which tells that there are some factors that influenced students' interest in reading such as: (1) external factors such as, the role of parents, infrastructure, and the influence of teacher. (2) internal factor, which is theirself like their ability in reading. And the strategy reading aloud that been carried out by the teacher to the fourth grade students was running effectively, students looked excited when the teacher asked them to read and some even took the initiative to read.